A Comparative Clinical-Bacteriological Study to Evaluate the Effect of Number of Visits on Bacterial Content in Necrotized Canals with No Apical Lesions" (Journal of Hama University, 2022)
the purpose was to compare the effect of number of visits (1-visit, 2-visits with calcium hydroxide (Ca(OH)2) dressing for 7 days) on bacterial count in necrotized root canals with no apical lesions.40 patients were recruited for the study. Teeth selected (n=40) were all single-canaled, single-rooted with necrotized pulp and no apical lesions. Teeth were divided into 2 groups (n1=n2=20) based on treatment method. Bacterial samples were collected from canals before preparation (S1). Preparation in both groups was done using rotary and hand files with NaOCl (5.25%) and EDTA (17%) as irrigants, CHX (0.2%) was used in the final rinse after preparation. Root canals in group I were treated in a single visit, while using a two-visits approach in group II. An intracanal dressing of (Ca(OH)2) was then applied in root canals of group II for 7 days. Samples were collected from root canals before filling (S2) in group I. Whereas in group II, they were collected after dressing was removed. Samples were transported to bacteriology lab in fluid thioglycolate transport medium, and later were cultured on blood agar and then incubated in aerobic conditions for 24 hours. Colony forming units (CFU) were counted and bacterial reduction between S1 and S2 was analyzed for each group and then compared.none of the treatment methods rendered the root canals bacteria-free. Single visit treatment technique had bacterial reduction medium of (75.13%), whereas 2 visits treatment with calcium hydroxide dressing achieved (82.36%) bacterial reduction. The difference was statistically significant (p